Strongly Summable Vector-Valued Sequence Spaces Defined by 2-modular - Nurnugroho, Burhanudin Arif; Prasetyo, Puguh Wahyu (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2021)
Summability is an important concept in sequence spaces. One summability concept is strongly Cesaro summable. In this paper, we study a subset of the set of all vector-valued sequence in 2-modular space. Some facts that we investigated in this paper include linearity, the existence of modular and completeness with respect to these modular.